Psychological Aspects of The Main Character in The “FEEL THE BEAT” Movie - Rifatun Nikmah, Rifatun Nikmah; Rezky, Revi Ayu; Ariansyah, Riyo Tegar; Wahyuni, Winda; Afas, Muhamad Zainuddin; Hadziq Fikri, Arief (English Education Program, Education Faculty, Universitas Nurul Huda, 2023)
This study discuss about the analysis of the psychological aspects for human motivation of the main character in the “Feel the Beat”movie, which aims to find out some psychological aspects of the main character in the movie. The data in this study were taken from the “feel the beat” movie using the documentation method, and the data that had been obtained were analyzed using a qualitative descriptive method. Data were collected by using documentation, making sure the conversation, understanding the content of the movie, and taking note. Data were analyzed by using data reduction, data display and data conclusion. The results of the data analysis reveal that the main character has all psychological aspects of human motivation in her life. There are 12 data that refer to these five aspects. 1 (8,33%) data representing appetites, 1 (8,33%) data referring to the want aspect, 6 (50%) data referring to the emotions aspect, 3 (25%) data referring to refers to aspects of feeling and attitude, 1(8,33%) data refers to aspects of social motive.